2020
DOI: 10.3390/su12198124
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Capital, Workload, and Burnout: What’s New? The Impact of Personal Accomplishment to Promote Sustainable Working Conditions

Abstract: Research on burnout has traditionally focused on job demands, with less attention paid to protective factors. From the emerging and innovative area of psychology of sustainability and sustainable development, this study aimed to analyze the relationship that job demands (workload), and personal resources (psychological capital) have with burnout. The sample includes 517 workers from various professional sectors. Results of the structural equation analysis show that (1) psychological capital and workload are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 68 publications
(113 reference statements)
5
43
1
5
Order By: Relevance
“…In the study of Ding et al (2015), they found a negative and significant relationship between optimism and depersonalization. Similarly, the study conducted by Rehman et al (2017) and the study of Lopez-Nunez et al (2020) found negative relations. Hypothesis 5 was formed based on these findings and theoretical framework.…”
Section: Relationships Between Psycap and Burnoutmentioning
confidence: 76%
See 2 more Smart Citations
“…In the study of Ding et al (2015), they found a negative and significant relationship between optimism and depersonalization. Similarly, the study conducted by Rehman et al (2017) and the study of Lopez-Nunez et al (2020) found negative relations. Hypothesis 5 was formed based on these findings and theoretical framework.…”
Section: Relationships Between Psycap and Burnoutmentioning
confidence: 76%
“…Previous studies were examined and different results were found. Rehman et al (2017) and Lopez-Nunez et al (2020), found a positive and significant relationship, while Ding et al (2015) found a negative and significant relationship. In the same study, it was concluded that optimism negatively and significantly affected decreased personal accomplishment.…”
Section: Relationships Between Psycap and Burnoutmentioning
confidence: 87%
See 1 more Smart Citation
“…Stress can be broadly defined as “an emergent process that involves interactions between individual and environmental factors, historical and current events, allostatic states, and psychological and physiological reactivity” [ 125 ] (p. 1). Mental workload, in particular, can be viewed as a form of task-related or occupation-related stressor [ 126 ]. Mental workload can be objectively defined as the cost of internal resources (i.e., mental effort) to perform at a certain level or complete a task [ 127 , 128 , 129 ].…”
Section: Issues and Implicationsmentioning
confidence: 99%
“…On the other hand, JB is also an important factor in influencing organizational sustainability because JB can negatively affect performance, competitive advantage, and employee retainment rate [4,5]. JB has long been recognized as an occupational hazard for people-oriented professions [6,7]. JB is a state of physical, emotional, and mental exhaustion in employees who work with people in emotionally demanding situations [8].…”
Section: Introductionmentioning
confidence: 99%